Complex network analysis of spatiotemporal dynamics of premixed flame in a Hele-Shaw cell: A transition from chaos to stochastic state - Nomi, Yuji; Gotoda, Hiroshi; Fukuda, Shingo; Almarcha, Christophe (Chaos (Woodbury, N.Y.), 2021)
We study the dynamical state of a noisy nonlinear evolution equation describing flame front dynamics in a Hele-Shaw cell from the viewpoint of complex networks. The high-dimensional chaos of flame front fluctuations at a negative Rayleigh number retains the deterministic nature for sufficiently small additive noise levels. As the strength of the additive noise increases, the flame front fluctuations begin to coexist with stochastic effects, leading to a fully stochastic state. The additive noise significantly promotes the irregular appearance of the merge and divide of small-scale wrinkles of the flame front at a negative Rayleigh number, resulting in the transition of high-dimensional chaos to a fully stochastic state.